Wardah Dari Pandangan Mahasiswa: Antara Kesadaran, Citra, dan Keputusan Pembelian Cushion - Rohman, Fadillah Fatqur; Safanah, Melati Nur; Sari, Novia Fatikhah; Zharifah, Sabnita La'aili Nur; Riswari, Syifa Destiana; Hasanah, Uswatun Nur (UNIVERSITAS MARITIM AMNI SEMARANG, 2025)
This research attempts to evaluate the impact that brand awareness and brand image have on the purchase decision of Wardah cushion products by Economic Education students of UNS. The sample size consisted of 71 respondents which were collected using purposive sampling technique. Analysis performed included multiple linear regression, classical assumption tests (normality, multicollinearity, heteroscedasticity), t test, F test, and coefficient of determination in SPSS 2022. Results from the analysis indicated that both components, brand awareness and brand image of the Wardah products, separately (partially) yield positive and significant influences on the purchase decision. Moreover, in a concurrent (simultaneous) approach both factors still significantly contribute towards the purchase decision.